Neuropsychological effects of exposure to naphtha among automotive workers. Issue 2 (February 1994) - White, R F; Robins, T G; Proctor, S; Echeverria, D; Rocskay, A S
Abstract : The association between exposure to naphtha and neurobehavioural measures was examined prospectively over one year among workers employed at an automotive plant that used naphtha to calibrate fuel injectors. The neurobehavioural tests included those that assess mood, basic intelligence, and functioning of the cerebral frontal lobes and limbic system and were designed so that acute, reversible, and chronic effects of solvent exposure could be assessed. Participants were 248 workers in June 1988, and the testing was repeated on 185 of these workers in 1989. Concentrations of naphtha at the plant ranged from six to 709 mg/m3, although exposure was greater in 1988 than in 1989. Duration of exposure for individual subjects ranged from 0.8 to 7.3 years. Cross sectional data analyses showed significant associations between level of exposure to naphtha and slower timed scores on trails A, and greater reports of negative affective symptoms on profile of mood states scales in 1988 but not 1989. Threshold model analyses of the 1989 data showed an association between score on visual reproductions immediate recall and daily exposure to naphtha at or above 1050 h x mg/m3. Models of chronic exposure showed no associations between chronic exposure and negative neurobehavioural outcome. Results suggest that naphtha produces mild acute reversible effects on function of the central nervous system at or above daily exposures of 540 h x mg/m3 (approximately 90 ppm/h).